The Role of Social Media in Shaping Digital Entrepreneurial Intention and Innovation: A Comparative Study among Youth and Women Entrepreneurs - Chandra, Bobby; Nesya Aulia Putri Pajar; Icksansyah; Eka Fissagita (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
This study investigates the role of social media in shaping digital entrepreneurial intention and innovation, with a specific focus on youth and women entrepreneurs. Drawing from a systematic review of 20 academic articles, the paper identifies core themes, including the influence of social media platforms on entrepreneurial behavior, the reduction of traditional barriers for women, and the role of digital feedback loops in fostering innovation. The review reveals that while social media benefits both groups, youth are often motivated by visibility and trend dynamics, whereas women emphasize trust and community. These findings suggest that tailored digital strategies and support mechanisms are crucial to maximize social media’s entrepreneurial potential across demographics.